An Efficient and Optimized Backoff Scheme for Disseminating Heterogeneous Traffic for Multiple Instances of LLN-Based Industrial IOT Networks. - Animesh Giri (International Journal of Intelligent Systems and Applications in Engineering, 2024)
With numerous devices being connected to the Internet to create a network of smart things, the Internet of Things (IoT) has experienced rapid growth in recent years. However, because of their constrained power, processing, and bandwidth, these devices frequently require assistance with network efficiency and dependability. In order to overcome the difficulties of distributing heterogeneous traffic across numerous instances of low power and Lossy-IoT networks, this research suggests an effective, optimized backoff scheme. The suggested method makes use of backoff algorithms in conjunction with network coding to increase network efficiency and reliability while decreasing transmission delay. The binary exponential-backoff (BEB) algorithm and the truncated binary exponential backoff (TBEB) algorithm are two of the backoff algorithms used in the suggested scheme. The BEB algorithm is used to resolve collisions during transmission, while the TBEB algorithm is used to reduce the backoff stage and the transmission delay. The suggested scheme also makes use of network coding, which raises the network’s dependability by enabling multiple nodes to work collectively to transmit data, reducing the likelihood of data loss, and guaranteeing that the data reaches its target location. Extensive simulations are used to evaluate the performance of the proposed scheme, and the results show that it performs better than traditional backoff algorithms in terms of network efficiency, reliability, and transmission delay. The outcomes also show that the suggested method can manage heterogeneous traffic, which qualifies it for IoT networks with a variety of devices and applications. In conclusion, the suggested effective, optimized backoff scheme offers a potentially viable answer to the problems faced by lossy, low-power IoT networks. The scheme’s combination of backoff algorithms and network coding enhances network efficiency and reliability while reducing transmission delay, making it an attractive option for IoT network deployments.